Code Switching and Mixing Among Students at Catholic University of Saint Thomas - Karisma Erikson Tarigan; Bonar Gurning; Rosa Maria Simamora (CV. Rustam, 2024)
This study investigates the linguistic patterns of code-switching and code-mixing between Bahasa Indonesia and Batak languages among students at Catholic University of Saint Thomas to explore their impact on academic and social communication. The study utilizes a qualitative descriptive approach grounded in ethnographic and discourse analysis frameworks to examine natural interactions within WhatsApp group chats and face-to-face communications. These frameworks allow for an in-depth understanding of the dynamics of bilingual usage and the social functions of language switching in real-life contexts. The study identifies several typical patterns: frequency of switching correlates with the formality of the setting, with more frequent switching in informal contexts, and functional usage where students switch languages to clarify concepts or strengthen social bonds. The analysis reveals that 70% of bilingual students report positive social impacts from code-switching, such as enhanced communication efficiency, cultural identity expression, and academic collaboration. However, 30% of student’s experience anxiety or feelings of exclusion due to limited fluency in dominant languages, which affects their sense of belonging and academic engagement. These findings highlight the dual nature of code-switching as both a facilitator of communication and a potential barrier in multilingual environments. The study suggests that educational policies at the University of Saint Thomas should support a more inclusive multilingual environment to address the diverse linguistic needs of all students, thereby enhancing cognitive, emotional, and social outcomes.